Vulneración del derecho a la tutela jurisdisccional efectiva en la procedencia de admisión de demanda por reducción, variación, prorrateo o exoneración de alimentos contenidas en el Art. 565-A del C. P. C. - Patiño La Rosa, Jair Alexander (2018)
The present thesis titled "The violation of professors' rights at public universities", has as the main problem: How does the ambiguity in the interpretation of Article 132° of the Law 30220, a product of a bad legal technique, violates the recognized constitutional rights of professors at public universities?, besides, it has as the main objective: To carry out an analytical study of a propositional type on the ambiguity in the interpretation of Article 132° of the Law 30220, as a result of an inadequate legal technique, and the violation of the recognized constitutional rights of professors at public universities. Following the methodological concepts of San Pieri (2006), we can identify that this research presents a transectional, descriptive and correlational nature; since, at first place, we will search to validate the knowledge from the analysis of a professor´s reality at Peruvian public universities in the last decade, to then measure the degree of relation between his participation in the administrative management of public universities and the low standards of quality in the educational services that have been provided to universities students, with the object of defining why the Peruvian legislator considered necessary to stablish a prohibition to the professors at public universities in accordance to Article 132° of the University Law. The population for the survey was 42 people, within lawyers with specialization in constitutional law, with an optimal sample of 40 professionals, they were part of interviews, debates and analysis of cases. The statistical treatment was carried out by the use of pie charts.